Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.